Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Isolation and complete genome sequence of Halorientalis hydrocarbonoclasticus sp. nov., a hydrocarbon-degrading haloarchaeon - Dahe Zhao; Sumit Kumar; Jian Zhou; Rui Wang; Ming Li; Hua Xiang (Extremophiles, 2017)

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Holocene activity evidence on the southeast boundary fault of Heqing basin, middle segment of Heqing-Eryuan fault zone, West Yunnan Province, China - Chang-bin Sun; De-wen Li; Xiao-ming Shen; Yan-rui Kang; Rui Liu; Ya-jiao Zhang (Journal of Mountain Science, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Research and application of spectral inversion technique in frequency domain to improve resolution of converted PS-wave - Hua Zhang; Zhen-Hua He; Ya-Lin Li; Rui Li; Guamg-Ming He; Zhong Li (Applied Geophysics, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)